Using Block Model Approach in Enhancing Pupils’ Word Problem Solving Performance - Baluyos, Genelyn (EduLine: Journal of Education and Learning Innovation, 2025)
The Block Model Approach plays a vital role in the pupils' problem-solving performance in Mathematics. This experimental study investigated the effectiveness of the Block Model Approach in improving problem-solving skills among Grade 2 pupils in a public school in Misamis Occidental. Using the Solomon Four-Group Experimental Design, 40 pupils were randomly assigned to experimental and control groups, with pretest and posttest measures. A researcher-made 20-item Word Problem Solving Test was used to assess students' performance. Data were analyzed using mean, standard deviation, t-test, and two-way ANOVA. The findings revealed that, in the pretest, most pupils in both groups did not meet expectations, with the experimental group slightly outperforming the control group. After using the Block Model Approach, the control group showed minimal improvement, while the experimental group demonstrated substantial progress, with many pupils reaching satisfactory levels. A significant difference between the experimental and control groups in pretest and posttest performance underscored the Block Model Approach's effectiveness. However, no significant differences were observed between the control or experimental groups, suggesting that the pretest did not impact the outcomes. The Block Model Approach independently contributed to the improved performance of the experimental group. Therefore, using the Block Model Approach can effectively enhance problem-solving abilities in elementary mathematics education. Math teachers may adopt the Block Model Approach to promote equitable learning and enhance problem-solving skills, regardless of students’ prior knowledge. Keywords: Block Model Approach, intervention strategies, Mathematics education, problem-solving, Solomon Four-Group Design